Identification of Leaflet Using Pixel Tracker Technique in Echocardiogram - Nasir N.R.M.; Rahmat R.W.O.K.; Sulaiman P.S.; Kadiman S.; Dimon M.Z. (Springer Verlag, 2023)
Decision making; Diagnosis; Echocardiography; Petroleum reservoir evaluation; Pixels; Surgery; Tracking (position); 3D echocardiography; Decision making process; Medical fields; Surgical techniques; Tracking techniques; Transesophageal (TEE); Transesophageal echocardiographies; Tricuspid valve; Image enhancement